2018
DOI: 10.1038/s41598-017-18862-1
|View full text |Cite
|
Sign up to set email alerts
|

Human mesenchymal stem cells lose their functional properties after paclitaxel treatment

Abstract: Mesenchymal stem cells (MSCs) are an integral part of the bone marrow niche and aid in the protection, regeneration and proliferation of hematopoietic stem cells after exposure to myelotoxic taxane anti-cancer agents, but the influence of taxane compounds on MSCs themselves remains incompletely understood. Here, we show that bone marrow-derived MSCs are highly sensitive even to low concentrations of the prototypical taxane compound paclitaxel. While MSCs remained metabolically viable, they were strongly impair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 52 publications
2
31
1
Order By: Relevance
“…Analyses reporting the influence of taxanes on MSCs have produced inconsistent results. While paclitaxel treatment was shown to decrease MSC proliferation in a dose‐dependent manner in some publications, other studies showed uniform reduction in cell numbers with no dose‐dependent effects . The MSCs' proliferative ability seems strongly impaired by paclitaxel treatment, although the stem cells remained metabolically viable even after exposure to high doses .…”
Section: Effects Of Chemotherapeutic Anti‐cancer Agents On Mscsmentioning
confidence: 99%
See 3 more Smart Citations
“…Analyses reporting the influence of taxanes on MSCs have produced inconsistent results. While paclitaxel treatment was shown to decrease MSC proliferation in a dose‐dependent manner in some publications, other studies showed uniform reduction in cell numbers with no dose‐dependent effects . The MSCs' proliferative ability seems strongly impaired by paclitaxel treatment, although the stem cells remained metabolically viable even after exposure to high doses .…”
Section: Effects Of Chemotherapeutic Anti‐cancer Agents On Mscsmentioning
confidence: 99%
“…On a molecular level, up‐regulation of TNF‐α after paclitaxel treatment was found associated with increased apoptosis in MSCs . Additionally, it has been demonstrated that paclitaxel resulted in a significant increase of premature senescence in MSCs, explaining the stem cells' observed preservation of viability despite a strong reduction in proliferation . Contrary to alkylating agents, methotrexate and arsenic trioxide, paclitaxel led to a long‐lasting suppression of cell growth after withdrawal of the drug .…”
Section: Effects Of Chemotherapeutic Anti‐cancer Agents On Mscsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistently, oxidative stress-induced expression of these senescence-associated markers was significantly attenuated by SHH treatment (Figures S4A and S4B). As decreased proliferative 28 and migratory 29 capacities are well-known senescence-associated phenotypes in multiple cell types of adult stem cells, we investigated whether SHH alleviates senescence-induced stem cell dysfunctions in vitro. As shown in Figures 1D and 1E, SHH markedly alleviated senescence-induced suppressive effects on the growth and migration of endometrial stem cells.…”
Section: Shh Alleviates Various Aging-associated Endometrial Stem Celmentioning
confidence: 99%